2016
DOI: 10.1111/jcpe.12586
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant crevicular fluid biomarkers as discriminants of peri‐implant health and disease

Abstract: PICF biomarkers might help discriminate peri-implant health from disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Inflammation in the peri‐implant tissues may be latent in the early stages and not readily detected by clinical measures. Therefore, PICF analysis might provide valuable information for the early diagnosis of inflammatory changes and might even serve as a tool for determination of patient susceptibility . Although differences were observed with the control site measurements at 3 and 6 months, particularly for the EOC sites the present study revealed similar biomarker and microbiological data in the PICF samples obtained from the EOC and IOC sites.…”
Section: Discussionsupporting
confidence: 89%
“…Inflammation in the peri‐implant tissues may be latent in the early stages and not readily detected by clinical measures. Therefore, PICF analysis might provide valuable information for the early diagnosis of inflammatory changes and might even serve as a tool for determination of patient susceptibility . Although differences were observed with the control site measurements at 3 and 6 months, particularly for the EOC sites the present study revealed similar biomarker and microbiological data in the PICF samples obtained from the EOC and IOC sites.…”
Section: Discussionsupporting
confidence: 89%
“…Among the 19 included studies, five used ELISA R&D System; a type of sandwich immunoassay where two highly specific antibodies are used to detect a target analyte . Eight used other ELISA kits, two CBA assays, three multiplexes, and one Luminex kit …”
Section: Resultsmentioning
confidence: 99%
“…Limited evidence exists to show the number of subjects with a sufficient sample size; that is, no calculations of statistical power were documented. Among the 19 included studies, only few studies accounted for smoking habits, although smoking has been identified as a risk indicator for peri‐implant inflammation . Other limitations include but are not limited to no consideration of other potential risk indicators for PI, such as history of periodontitis and tissue phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase‐9 (proteolytic enzyme) and IL‐1β (cytokine) have proinflammatory effect that appears to have a central role in peri‐implant tissue destruction . The biological effects of IL‐1β depend on its tissue concentration.…”
Section: Discussionmentioning
confidence: 99%